ASPECTS OF ECONOMIC PRODUCTION IN MALAY CLASSICAL LITERATURE ACCORDING TO SHEIKH DAUD AL-FATANI - Hadenan Towpek; Joni Tamkin Borhan (Graduate Program of Pontianak Institute of Islamic Studies, 2012)
Sheikh Daud bin ‘Abdullah al-Fatani (1131-1265AH/1718-1847CE) is a Malay scholar who appears on the transition period to 18M and 19M century. He was known as a productive scholar and prolific book, which can be viewed from various aspects. Therefore, this article attempts to analyze his views on aspects of production as discussed in his masterpiece Furu‘al-Masa’il and specifically referred to in chapter transaction. This article uses content analysis methods through a thematic approach in identifying the aspects of production. This article identifies at least nine aspects contained in the production of the work of priority in economic aspect, the aspect of work/effort, capital, profit-generating aspect, the aspect of profit distribution, aspects of joint agricultural projects, exploring aspects of soil, aspect prohibition of usury and aspects of the general offer. This finding indirectly indicates that the views of Sheikh Daud al-Fatani presented in the book furu‘ al-Masa’il are an ever green that is a deep insight into and remain relevant from the past, present and future. Key Words: Economic, Production, Malay, Daud Al-Fatani